Research progress and advances in endoplasmic reticulum stress regulation of acute kidney injury - Li-Ran Zhu; Wei Cui; Hai-Peng Liu (Renal Failure)
Acute kidney injury (AKI) is a common and severe clinical disorder in which endoplasmic reticulum (ER) stress plays an important regulatory role. In this review, we summarize the research progress on the relationship between ER stress and AKI. It emphasizes the importance of maintaining a balance between promoting and protecting ER stress during AKI and highlights the potential of ER stress-targeted drugs as a new therapeutic approach for AKI. The article also discusses the need for developing drugs that target ER stress effectively while avoiding adverse effects on normal cells and tissues. The review concludes that with a more comprehensive understanding of ER stress mechanisms and advancements in research techniques, more effective treatment options for AKI can be developed in the future.